Job search, human capital and wage inequality - Carlos Carrillo-Tudela (University of Essex, Institute for Social and Economic Research (ISER), 2012)
This paper constructs and quantitatively assesses an equilibrium search model with on-the- job search and general human capital accumulation. In the model workers differ in their innate abilities and firms in their productivities. Wages are dispersed because of search frictions and workers' productivity differentials. Using the (log) wage variance decomposition implied by the model I show that wage inequality among low skilled workers is mostly driven by differ- ences in their productivities. Among medium skilled workers, productivity differentials and search frictions are equally important. The model reproduces the observed cross-sectional wage distribution, the average wage-experience profile and the observed Mean-min ratio.
Keywords: J63; J64; J41; J42; 330; Job search; human capital accumulation; wage dispersion; turnover